A rare craniofacial anomaly associated with balanced reciprocal translocation between chromosome 1 and 7: a case report - Antil, Amit; Kumar, Umesh; Ray, Saugat; Chakrabarty, Barun K.; Singhal, Paresh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
The occurrence of balanced reciprocal translocation of chromosome 1 and 7 is one of the rare anomalies. The present case report focuses on a case of 07-year-old male patient with craniofacial anomaly due to balanced reciprocal translocation of chromosome 1 and 7 manifesting as microcephaly, microstomia, oligodontia and scrotal hypospadias with bilateral retractile testis. The patient had severe retrognathic and hyperdivergent mandible along with multiple carious and unerupted permanent teeth. After complete oral prophylaxis of the patient, the restorations of all carious teeth were carried out. Extraction of root stumps under conscious sedation has been planned in later phase. The patient will further be followed up for orthodontic correction of maxillary and mandibular arches in all three planes keeping in view of the growth status of the patient. The present case report intends to provide an overview of the clinical and radiographical features of this rare anomaly who need a prolonged interdisciplinary management and long term follow up. Further, this will add value to the existing prevalence in the available literature.